Association of Gestational Weight Gain With Maternal and Infant Outcomes: A Systematic Review and Meta-analysis. Issue 10 (October 2017) - Goldstein, Rebecca F.; Abell, Sally K.; Ranasinha, Sanjeeva; Misso, Marie; Boyle, Jacqueline A.; Black, Mary Helen; Li, Nan; Hu, Gang; Corrado, Francesco; Rode, Line; Kim, Young Ju; Haugen, Margaretha; et al.
Abstract : (Abstracted from JAMA 2017;317(21):2207–2225) Gestational weight gain (GWG) in excess of Institute of Medicine (IOM) guidelines has been associated with adverse pregnancy outcomes including preeclampsia, postpartum weight retention, and offspring obesity. Prevalence of obesity and excess GWG are becoming more prevalent from 40% in 2013 to 2014, with more than 50% of obese pregnant women gaining gestational weight greater than IOM GWG recommendations in a US study from 2002 to 2008.